2020
DOI: 10.31557/apjcp.2020.21.5.1235
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Instability in Peripheral Blood and Buccal Mucosal Cells of Marijuana Smokers: The Impact of Tobacco Smoke

Abstract: The inhalation promoted by cigarettes in dry form is widely used due to greater effectiveness. It is estimated that 0.5-1 g of the plant contains 20 mg of THC. This in turn is consumed in the form of tetrahydrocannabinolic acid as a result of combustion of the plant (Bonfa et al., 2003). The acid then converts into free THC, where it is absorbed through inhalation; the smoke goes to the lungs allowing the bioactive substances to reach the bloodstream and central nervous system (Bonfa et al., 2003). Marijuana i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…In contrast, low doses of THC are usually not associated with genotoxicity ( 20 , 47 49 ). Interestingly and similar to our results, Souza et al, reported genetic damage in PBLs from marijuana users using a comet assay, and increased MNs in the buccal mucosa of marijuana and tobacco users but not in marijuana mono-users, in comparison to a control group ( 50 ). It is important to highlight that the consumption of tobacco per se can potentiate the amount of damage, on a dose-dependent fashion ( 51 – 53 ), thus our results suggest that tobacco consumption could potentiate the effects of marijuana.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, low doses of THC are usually not associated with genotoxicity ( 20 , 47 49 ). Interestingly and similar to our results, Souza et al, reported genetic damage in PBLs from marijuana users using a comet assay, and increased MNs in the buccal mucosa of marijuana and tobacco users but not in marijuana mono-users, in comparison to a control group ( 50 ). It is important to highlight that the consumption of tobacco per se can potentiate the amount of damage, on a dose-dependent fashion ( 51 – 53 ), thus our results suggest that tobacco consumption could potentiate the effects of marijuana.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the mode of consumption and administration of marijuana might be responsible for the discrepancies observed on the reported effects of marijuana ( 50 ), and evidence suggest that the protective effects of marijuana are lost when it enters the body through the respiratory tract, similar to tobacco smoke, and then its harmful effects might appear. In fact, marijuana and tobacco smoke show striking similarities in terms of their physical and chemical properties ( 15 , 16 , 54 ), several of them classified as carcinogenic by the IARC ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…BMCyt assay use has spread widely since it is minimally invasive, painless, easily accessible, and represents the first barrier cells of the respiratory and digestive tracts, furthermore, it is considered a marker of some systemic conditions (Celik et al, 2010; Kashyap & Reddy, 2012). In addition, BMCyt assay is a predictive marker, that evaluates nuclear anomalies associated with genotoxicity (micronucleus [MNs] and nuclear buds [NBUDs]), stages of early (abnormally condensed chromatin [CC]) and late (karyorrhexis [KR]) apoptotic processes, alternative forms of nuclear disintegration (pyknotic nuclei [PN]), cytokinesis defects (binucleated cell [BN]), and advanced stages of cell death (karyolysis [KL]), and their increase is associated with genotoxic and cytotoxic processes, and cancer (Bolognesi et al, 2013; Burgaz et al, 2011; Fenech et al, 2011; Holland et al, 2008; Malacarne et al, 2021; Motgi et al, 2014; Souza et al, 2020; Stich & Rosin, 1983; Thomas & Fenech, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the BMCyt assay is employed as a predictive marker, as micronuclei and other nuclear abnormalities (NA) serve as indicators of DNA damage and cell death. Their increase is associated with genotoxic, cytotoxic, and cancerous processes [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%